Intellectual human capital, corporate social innovation and sustainable development: A conceptual framework - Amran A.; Yon L.C.; Kiumarsi S.; Jaaffar A.H. (Inderscience Publishers, 2023)
Personnel; Sustainable development; Business and societies; Conceptual frameworks; Corporate research; Intellectual human capitals; Management control system; Resource-based view; Strong sustainability; Sustainability issues; Man machine systems